PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN KUALA ENOK INDRAGIRI HILIR - Sari Kumala Daima; Ningsih Suryati Dewita; Tarigan Aprilina Mida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of work discipline, work motivation, and workenvironment on the performance of employees of PT PLN (Persero) Kuala EnokCustomer Service Unit Indragiri Hilir. The population in this study were employees of PTPLN (Persero) Customer Service Unit Kuala Enok Indragiri Hilir, as many as 108people. The sampling technique in this study used purposive sampling, namely 50 officeemployees. Sources of data used are primary data collected by distributingquestionnaires as research instruments. and the analysis tool is multiple linear regressionanalysis through the SPSS For Windows 25 program. With employee performance as thedependent variable and three independent variables, namely work discipline, workmotivation, and work environment. The results of this study indicate that: 1) Workdiscipline has a significant effect on employee performance, 2) Work motivation has asignificant effect on employee performance and 3) Work environment has a significanteffect on employee performance. Keyword : Work Discipline, Work Motivation, Work Environment, EmployeePerformance